Uterine B-cell lymphoma in two dogs – a case report - Novotný, Ladislav; Taylor, Frances; Claxton, Katherine; Dudova, Jana; Hanshaw, Daren; Misik, Jan (Acta veterinaria Brno, 2017)
Uterine lymphoma is rare in the dog, in other animal species, and in humans. The lymphoma in the two female dogs presented as a primary tumour of uterine tissue and was classified as diffuse centroblastic B cell lymphoma. Terminally, the uterine lymphoma metastasized to various organs in one of the dogs, despite chemotherapy. This case study describes a very rare form of canine lymphoma and suggests to include lymphoma in the differential diagnoses in bitches with uterine masses.
Keywords: nádory močového měchýře; B-buněčný lymfom; Lymphoma, B-Cell; Dog Diseases; Urinary Bladder Neoplasms; nemoci psů